The Moderating Role of Goal Orientation in the Relationship Between Self-Efficacy, Peer Support, and Academic Resilience Among University Students - Antonina Pantja Juni Wulandari; Bernadette Narulina Setiadi; Theresia Indira Shanti; Charli Sitinjak (Bulletin of Counseling and Psychotherapy, 2025)
Academic resilience refers to an individual's ability to cope with pressures within the academic environment and to recover from setbacks or adverse situations. It is influenced by both internal and external factors. Previous research has extensively examined self-efficacy as an internal factor and peer social support as an external factor contributing to academic resilience. This study explores the psychological mechanism underlying these relationships by introducing goal orientation as a moderating variable in the influence of self-efficacy and peer support on academic resilience. The types of goal orientation examined include learning goal orientation, avoiding goal orientation, and proving goal orientation. A moderation test was conducted using hierarchical regression analysis with a sample of 1,082 university students from a private higher education institution in Jakarta. The findings revealed that both learning goal orientation and avoiding goal orientation significantly strengthened the effect of self-efficacy on academic resilience, while proving goal orientation significantly weakened this relationship. These results suggest that goal orientation can be leveraged to support students who have trouble adjusting during the early stages of university life. However, the study also found that goal orientation did not significantly moderate the relationship between peer social support and academic resilience. It is suggested that this may be due to the inherently strong role of peer relationships among individuals in this age group, reducing the influence of goal orientation in their adaptation process to university settings.